Empowerment of tourism awareness groups in managing hot spring tourism in Nyelanding Village - Muhammad Amsal; Akifah Nurfadhilah Djamil; Rivanda Baroqah Butang; Leni Puspitasari; Emikawati Emikawati; Cindy Permatasari; Ria Agustia; Syifa’ul Husna; Firdzan Mahasdin Sabdan; Nurul Aulia Suryani T; Irene Tresna Wiati (Universitas Muhammadiyah Magelang, 2023)
South Bangka Regency boasts a unique tourist destination in the form of hot springs. However, these destinations have suffered from cleanliness issues and a lack of greenery, leading to a decline in tourist visits. Consequently, this community service program aims to educate tourism awareness groups on maintaining environmental cleanliness and enhancing greenery to revitalize the Nyelanding Village hot spring tourism area. The method employed involves assisting in the management of tourist destinations. The result of implementing this empowerment initiative is a cleaner and more beautiful environment, with the long-term benefit of a greener surroundings around the hot springs.